Analisis Tindak Tutur Direktif dalam Novel Rumah Untuk Alie Karya Leen Liu (Kajian Pragmatik) - Fiti Pera; Ramadhan Kusuma Yuda; Aqis Yuliansyah (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study is to describe directive speech acts in the novel Rumah Untuk Alie by Lenn Liu. The research method is descriptive, a form of qualitative research, then the research setting is anywhere because it is descriptive qualitative, the research data is in the form of words, phrases, and sentences containing directive speech acts in the novel Rumah Untuk Alie by Lenn Liu, namely how are the directive speech acts of commanding, directive speech acts of begging, and directive speech acts of asking. The data source is the novel Rumah Untuk Alie by Lenn Liu which was published on February 27, 2024 with a thickness of 262 pages published by Tekad, Depok. The researcher used a documentary study technique. The data collection tool used by the researcher in this study was the researcher himself. The technique for checking the validity of the researcher's data used Triangulation, namely theory triangulation. The data found in this study amounted to 62 data, which included 21 commanding data, 17 begging data, and 24 requesting data.